Biorefining Waste Sludge From Water and Sewage Treatment Plants Into Eco-Construction Material - Cheng, Wai Nam; Yi, Haakrho; Yu, Chun-fai; Wong, Ho Fai; Wang, Guoxiang; Kwon, Eilhann E.; Tsang, Yiu Fai (Frontiers in Energy Research, 2019)
This study aims to investigate the feasibility of using different waste sludge and coal combustion residuals in eco-concrete block production. The compressive strength of the eco-concrete blocks produced by waterworks sludge, bottom and fly ashes were 36 MPa, which comply with the standard specifications for paving blocks in Hong Kong. The optimal mixing proportion (by weight) of different materials in the blocks such as aggregates, cementitious materials, water, and fly ash was 1.1: 1.0: 0.5: 0.22 respectively. The environmental and toxicological impacts of the final products were then evaluated according to the toxicity characteristic leaching procedure (TCLP). While several heavy metals (i.e., Hg, Cu, and Pb) have been identified in the specimens, the levels of these contaminants complied with Standards (US 40 CFR 268.48). Waste materials generated from water and sewage treatment processes and power plants are feasible to be used as ingredients for paving concrete block production. These products are environmentally acceptable and mechanically suitable for resource recovery of waste materials.